One-step, stereoselective synthesis of octahydrochromanes via the Prins reaction and their cannabinoid activities. Issue 9 (28th February 2018) - Slater, Shuneize; Lasonkar, Pradeep B.; Haider, Saqlain; Alqahtani, Moneerah J.; Chittiboyina, Amar G.; Khan, Ikhlas A.
Graphical abstract: Highlights: Stereoselective synthesis of octahydrochromanes were achieved with Prins reaction. Chiral homoallylic alcohols and benzaldehydes were utilized as starting materials. Stereospecificity and stereoselectivities for the newly created centers were explained. Newly synthesized octahydrochromanes were tested against both cannabinoid receptors. Abstract: Novel, functionalized octahydrochromane derivatives were synthesized in a single step via the Prins reaction. Enantiomerically pure (+)-isopulegol was reacted with benzaldehyde to stereoselectively yield the corresponding octahydro-2 H -chromen-4-ol derivative containing five stereocenters. A total of 10 compounds were synthesized by altering the enantiomer of isopulegol and the substituted benzaldehyde, and the resulting enantiopure octahydrochromanes were screened in vitro against the cannabinoid receptor isoforms CB1 and CB2. Compounds containing an olefin at the C4 position [(+)-3c, (−)-3c, (−)-7c, (−)-9c and (−)-11c ] of the octahydrochromane scaffold were found to exhibit reasonable displacement of [ 3 H] CP55, 940 from the CB receptors, whereas the corresponding hydroxy analogs [(+)-3a, (+)-3b, (−)-3a, (−)-3b and (+)-5a ] had very little or no effect.